Acute Splenic Artery Thrombosis and Infarction Associated with COVID-19 Disease - Osama Qasim Agha; Ryan Berryman (Case Reports in Critical Care)
Coronavirus 2019 disease (COVID-19) is a viral illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It emerged in Wuhan, China, in December 2019 and has caused a widespread global pandemic. The symptoms of COVID-19 can vary from mild upper respiratory symptoms to severe pneumonia with hypoxemic respiratory failure. Multiple studies and reports have reported a hypercoagulable state associated with this disease, and various recommendations have emerged to guide the use of anticoagulants for prophylaxis. We are reporting a case of symptomatic acute splenic thrombosis causing splenic infarction in a patient suffering from a severe case of COVID-19 and despite the use of an intermediate dose of low-molecular-weight heparin (LMWH). The patient was treated with full-dose anticoagulation and was eventually discharged home on a direct oral anticoagulant.